Fair Trade certified coffee estates: can Fair Trade USA promote workers' well-being, empowerment and gender equity in Brazilian and Nicaraguan coffee plantations? - Rosty, Claudia Magalhaes, author; Raynolds, Laura T., advisor; Hempel, Lynn, committee member; Carolan, Michael, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2019)
In 2012, Fair Trade USA began to certify coffee estates, previously restricted to small producer organizations, to expand the benefits of fair trade to hired laborers. This dissertation research analyzes the implications of the Fair Trade USA certification of coffee plantations in 1) bolstering workers' well-being, 2) empowerment, and 3) gender equity on certified coffee estates in Brazil and Nicaragua. Using a cross-national comparative design and multi-methods qualitative techniques, this study examines how the Fair Trade USA certification of coffee estates plays out differently within each national context. The findings suggest that Fair Trade USA fosters worker's well-being in coffee estates when operating below national labor legislation and sectoral standards, and indicate variation, unevenness and limitations in bolstering worker's empowerment. This research reports marginal gender equity impact on rural workers.
Keywords: fair trade certified coffee plantations; empowerment; Fair Trade USA